Prior stroke and transient ischemic attack as risk factors for subsequent stroke in atrial fibrillation patients: a report from the GARFIELD-AF registry - Hacke, Werner; Bassand, Jean-Pierre; Virdone, Saverio; Camm, A John; Fitzmaurice, David A; Fox, Keith AA; Goldhaber, Samuel Z; Goto, Shinya; Haas, Sylvia; Kayani, Gloria; Mantovani, Lorenzo G; Misselwitz, Frank; et al. (International journal of stroke, 2020)
Background: Its not always possible to verify whether a patient complaining of symptoms consistent with transient ischemic attack has had an actual cerebrovascular event.Research questionTo characterize the risk of cardiovascular events associated with a history of stroke/transient ischemic attack in patients with atrial fibrillation.Study design and methodsThis study investigated the clinical characteristics and outcomes of patients with a history of stroke/transient ischemic attack among 52,014 patients enrolled prospectively in GARFIELD-AF registry. The diagnosis of stroke or transient ischemic attack was not protocol defined but based on physicians? assessment. Patients? one-year risk of death, stroke/systemic embolism, and major bleeding was assessed by multivariable Cox regression.ResultsAt enrollment, 5617 (10.9%) patients were reported to have a history of stroke or transient ischemic attack. Patients with stroke or transient ischemic attack were older and had a greater burden of diabetes, moderate-to-severe kidney disease, and atherothrombosis and higher median CHA2DS2-VASc and HAS-BLED scores than those without history of stroke or transient ischemic attack. After adjustment, prior stroke/transient ischemic attack was associated with significantly higher risk for all-cause mortality (hazard ratio (HR), 1.26; 95% confidence interval (CI), 1.12?1.42), cardiovascular death (HR, 1.22; 95% CI, 1.01?1.48), non-cardiovascular death (HR, 1.39; 95% CI, 1.15?1.68), and stroke/systemic embolism (HR, 2.17; 95% CI, 1.80?2.63) than patients without history of stroke/transient ischemic attack. In patients with a prior stroke alone higher risk was observed for all-cause mortality (HR, 1.29; 95% CI, 1.11?1.50), non-cardiovascular death (HR, 1.39; 95% CI, 1.10?1.77), and stroke/systemic embolism (HR, 2.29; 95% CI, 1.83?2.86). No significantly elevated risk of adverse events was seen for patients with history of transient ischemic attack alone.InterpretationA history of prior stroke or transient ischemic attack is a strong independent risk factor for mortality and stroke/systemic embolism. This excess risk is mainly attributed to a history of stroke (with or without transient ischemic attack), whereas history of transient ischemic attack is a weaker predictor.Clinical trial registration: NCT01090362.